Analysis of the Effect of Zakat, Infaq and Shadakah (ZIS) Funds, GRDP and Regional Expenditure on Poverty in Nusa Tenggara Barat Province 2019-2022 - Erli Supiani; Busaini , Busaini; Siti Sriningsih (Tinta Emas Institute, 2024)
Poverty is a significant issue in developing countries, including Indonesia. Nusa Tenggara Barat is among the ten provinces with the highest number of impoverished people. This study aims to analyze the effects of ZIS Funds (Zakat, Infaq, Shadakah), GRDP, and Regional Expenditure on poverty in the regencies and cities of Nusa Tenggara Barat Province from 2019 to 2022. The research employs a quantitative approach and utilizes secondary data in the form of panel data, which consists of both time series data and cross-sectional data from 2019 to 2022. Data for this research is obtained through documentation methods, specifically the archival method, which involves sourcing information from books, agencies, institutions, and relevant sources related to the research. The secondary data is sourced from the BPS web, Baznas Statistics, and DJPB Kemenkeu. Panel data regression analysis, using the Fixed Effect Model (FEM) estimation method, is applied to analyze the data, with the assistance of the Eviews 10 program. The results indicate that, partially, the distribution of ZIS Funds has a positive but insignificant effect on poverty. The GRDP at constant prices (ADHK) has a negative and significant effect on poverty, while Regional Expenditure has a positive but insignificant effect on poverty in the regencies and cities of Nusa Tenggara Barat Province from 2019 to 2022. Simultaneously, the distribution of ZIS Funds, ADHK GRDP, and Regional Expenditure has a significant effect on poverty in the regencies and cities of Nusa Tenggara Barat Province from 2019 to 2022.